Single-cell analysis reveals that cryptic prophage protease LfgB protects Escherichia coli during oxidative stress by cleaving antitoxin MqsA - Laura Fernández-García; Xinyu Gao; Joy Kirigo; Sooyeon Song; Michael E. Battisti; Rodolfo Garcia-Contreras; Maria Tomas; Yunxue Guo; Xiaoxue Wang; Thomas K. Wood (Microbiology Spectrum, 2024)
ABSTRACTAlthough toxin/antitoxin (TA) systems are ubiquitous, beyond phage inhibition and mobile element stabilization, their role in host metabolism is obscure. One of the best-characterized TA systems is MqsR/MqsA of Escherichia coli, which has been linked previously to protecting gastrointestinal species during the stress it encounters from the bile salt deoxycholate as it colonizes humans. However, some recent whole-population studies have challenged the role of toxins such as MqsR in bacterial physiology since the mqsRA locus is induced over a hundred-fold during stress, but a phenotype was not found upon its deletion. Here, we investigate further the role of MqsR/MqsA by utilizing single cells and demonstrate that upon oxidative stress, the TA system MqsR/MqsA has a heterogeneous effect on the transcriptome of single cells. Furthermore, we discovered that MqsR activation leads to induction of the poorly characterized yfjXY ypjJ yfjZF operon of cryptic prophage CP4-57. Moreover, deletion of yfjY makes the cells sensitive to H2O2, acid, and heat stress, and this phenotype was complemented. Hence, we recommend yfjY be renamed to lfgB (less fatality gene B). Critically, MqsA represses lfgB by binding the operon promoter, and LfgB is a protease that degrades MqsA to derepress rpoS and facilitate the stress response. Therefore, the MqsR/MqsA TA system facilitates the stress response through cryptic phage protease LfgB.IMPORTANCEThe roles of toxin/antitoxin systems in cell physiology are few and include phage inhibition and stabilization of genetic elements; yet, to date, there are no single-transcriptome studies for toxin/antitoxin systems and few insights for prokaryotes from this novel technique. Therefore, our results with this technique are important since we discover and characterize a cryptic prophage protease that is regulated by the MqsR/MqsA toxin/antitoxin system in order to regulate the host response to oxidative stress.